2019
DOI: 10.1016/j.arr.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and health outcomes: An umbrella review of systematic reviews and meta-analyses of observational studies

Abstract: The aim of the present study was to map and grade evidence for the relationships between telomere length with a diverse range of health outcomes, using an umbrella review of systematic reviews with meta-analyses. We searched for meta-analyses of observational studies reporting on the association of telomere length with any health outcome (clinical disease outcomes and intermediate traits). For each association, random-effects summary effect size, 95% confidence interval (CI), and 95% prediction interval were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 72 publications
1
50
2
Order By: Relevance
“…A recent study from our lab using data from the National Health and Nutrition Examination Survey demonstrated that living in socioeconomically disadvantaged neighborhoods associated with shorter leukocyte telomere length among U.S. adults, indicating the potential impact of adverse neighborhood conditions on immune cells ( 63 ). It is important to note that leukocyte telomere length has also been reported to have inconclusive results for some diseases ( 64 ) and certainly warrants future research as racial/ethnic differences have been shown when comparing telomere length and/or telomere shortening rate of Blacks to those of Whites ( 65 67 ). Overall, urgent studies are needed to investigate cellular signaling mechanisms by which markers of social position, including socioeconomic position and the neighborhood environment of individuals ( 68 ), shape the transcriptional identity of immune cells ( 69 ) to further understand the disparities in COVID-19 outcomes and potential targets for therapeutic intervention.…”
Section: Markers Of Social Position and The Immune Systemmentioning
confidence: 99%
“…A recent study from our lab using data from the National Health and Nutrition Examination Survey demonstrated that living in socioeconomically disadvantaged neighborhoods associated with shorter leukocyte telomere length among U.S. adults, indicating the potential impact of adverse neighborhood conditions on immune cells ( 63 ). It is important to note that leukocyte telomere length has also been reported to have inconclusive results for some diseases ( 64 ) and certainly warrants future research as racial/ethnic differences have been shown when comparing telomere length and/or telomere shortening rate of Blacks to those of Whites ( 65 67 ). Overall, urgent studies are needed to investigate cellular signaling mechanisms by which markers of social position, including socioeconomic position and the neighborhood environment of individuals ( 68 ), shape the transcriptional identity of immune cells ( 69 ) to further understand the disparities in COVID-19 outcomes and potential targets for therapeutic intervention.…”
Section: Markers Of Social Position and The Immune Systemmentioning
confidence: 99%
“…Short telomere length, therefore, has been associated with compromised adult all-cause mortality (Wang, Zhan, Pedersen, Fang, & Hägg, 2018) and morbidity, including physical disorders, such as gastric cancer and diabetes, as well as psychological disorders, such as depression (e.g. Desai et al, 2018;D'Mello et al, 2015;Gillis et al, 2019;Lin, Epel, & Blackburn, 2012;Ridout, Ridout, Price, Sen, & Tyrka, 2016;Smith et al, 2019).…”
Section: Telomeresmentioning
confidence: 99%
“…p<0.05) were categorized into convincing, highly suggestive, suggestive, or weak evidence (class I to IV), following a grading scheme that has already been applied in various fields of medicine. [21][22][23][24][25][26][27][28][29][30][31][32][33] These criteria are fully reported in Supplementary Table 2.…”
Section: Grading the Evidencementioning
confidence: 99%